Kepemimpinan Kepala Sekolah dan Kinerja Guru di Era New Normal: Studi pada SMP Islam Al-Ikhlas Kota Jambi - Yulia Anggraini (JMiE (Journal of Management in Education), 2023)
This study aims to analyze the role of the principal in improving teacher performance in the New Normal era at SMP Islam Al-Ikhlas Kota Jambi, as well as to identify the challenges and efforts made in the process. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that: (1) the principal acts as a motivator, supervisor, and leader in managing teacher performance; (2) strategies applied include strengthening discipline, providing motivation, monitoring classroom performance, giving rewards to outstanding teachers, and conducting deliberations to resolve emerging issues; (3) challenges encountered involve teachers’ limited mastery of subject matter and difficulties in adapting to online learning, which hindered the effectiveness of the learning process.